Analysis of Content Marketing and Electronic Word of Mouth on the TikTok Platform Toward the Consumer Behavior of The Originote Products - Madyoratri, Maria Helena Putri; Susanti, Ety Dwi (Universitas Muhammadiyah Pontianak, 2025)
This study investigates the influence of content marketing and electronic word of mouth on the consumer behavior of The Originote products, especially among Generation Z in Surabaya. A quantitative approach with purposive sampling was applied, involving 100 respondents. Data were analyzed using multiple linear regression to examine both partial and simultaneous effects. The results reveal that both variables significantly influence consumer behavior. However, content marketing has a more dominant partial effect than electronic word of mouth. This indicates that content marketing is a more effective digital strategy in encouraging consumer behavior, particularly through engaging and well-designed content on TikTok